A case report of Evans Syndrome (Faridpur Medical College Journal, 2017)
Evans syndrome is a haematological disorder characterized by the sequential or simultaneous development of direct antiglobulin test (DAT) positive autoimmune haemolytic anaemia (AIHA), immune thrombocytopenia (ITP) and/or immune neutropenia in the absence of a known aetiology. No sex predilection is known. It may occur in all ethnic groups and all ages. This condition generally runs a chronic course and is characterized by frequent exacerbations and remissions. Here we report a case of a female who presented with both acute decompensated anaemia & thrombocytopenia. She received total 5 bags blood within 10 days for correction of anaemia but patients condition was deteriorating. CBC with PBF showed features consistent with immune haemolytic anaemia with thrombocytopenia, marked roulaeux formation and reticulocytosis. Direct Coomb's test (DAT) was positive and Indirect coomb's test was (IAT) negative. Her general condition was improved after injection methyl prednisolone for 3 days followed by oral prednisolone. Follow up CBC showed increased haemoglobin and platelet count without blood transfusion.Faridpur Med. Coll. J. Jul 2017;12(2): 88-91